The value relevance of the operacional leases - Pais, C. (2022)
So far, the operational leases are accounted as an expense and not as an asset but there is a proposal by the International Accounting Standards Board (IASB) to accounting them as finance lease because IASB believes that that improves the quality and comparability. So, I test whether the accounting of an operational lease as a finance lease is more value relevant to investors, whether this has changed over time and whether the operating lease liabilities is more value relevant for the investor. My results suggest for the largest European firms, that the investor incorporates the information of operating leases on the share price but I do not conclude that there was a change of this over time neither the liability is more value relevant than the asset. These results confirm that the accounting of the operational leases as a finance lease provides information which is much more useful.